Comparison of the Effectiveness of Duolingo and Cake Applications in Improving Students' English Language Proficiency - Telaumbanua, Yasminar Amaerita; Harefa, Selvin Try Hartati; Zebua, Mega Rohani; Zega, Sailas Mardianti; Zalukhu, Jepriaman; Mendrofa, Rejeki (Jurnal Penelitian Inovatif, 2024)
In this digital age, learning English is increasingly accessible through mobile apps. Duolingo and Cake are two popular apps that offer English language learning with different approaches. This study aims to compare the effectiveness of Duolingo and Cake apps in improving the English language skills of University of Nias. Using a causal comparative quantitative method, this study involved 20 University of Nias students as participants. Data was collected through pre and post learning tests to measure improvement in English language skills, particularly in terms of grammar and vocabulary. The results showed that the Duolingo application was more effective than Cake. The findings are expected to contribute to the development of application-based learning media in English language learning. However, Duolingo is more recommended for users who want to improve their grammar and vocabulary skills. Ultimately, this study concludes that Duolingo is recommended for users who want to improve grammar and vocabulary, while Cake can offer a more stable learning experience for those who seek consistency in practice. The urgency of this research lies in the increasing need for English language skills in the era of globalization. By knowing the relative effectiveness of the two apps, learners can choose the app that best suits their learning needs and preferences. In addition, the results of this study can also be a reference for language learning app developers in creating more relevant and effective features. The implication of this research is the importance of considering learners' individual characteristics in choosing learning media.